Remember Gerardas Žilinskas - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2010)
Reminescences about the doctoral studies of G. Žilinskas at the Manchester University and his work at Vilnius University.
Keywords: number theory; theorems on definite quadratic forms